Pro-vegetarian dietary patterns and mortality by all-cause and specific causes in an older Mediterranean population - Alejandro Oncina-Cánovas; Laura Torres-Collado; Manuela García-; Laura María Compañ-Gabucio; Sandra González-Palacios; Antonio J. Signes-Pastor; Jesús Vioque (Elsevier, 2024)
Purpose: Pro-vegetarian (PVG) dietary patterns have shown health benefits, although the evidence concerning their association with mortality is scarce, particularly in older populations. We investigated the effect of three defined PVG patterns on all-cause, cardiovascular disease (CVD) and cancer mortality risk in an older Mediterranean population. Methods: We analysed baseline data from 597 adults aged 65 and older who participated in a population-based cross-sectional study, and mortality during a 12-year period. We used a validated food frequency questionnaire to estimate the adherence in tertiles to three evidence-based PVG dietary patterns: a general PVG pattern (gPVG) and two specific variations (healthful -hPVG, and unhealthful -uPVG). The gPVG pattern incorporated data from 12 food groups, consisting of 7 plant-based and 5 animal-based. The hPVG and uPVG versions included information from 18 food groups (4 food groups added and the splitting of 2 food groups). We used Cox regression to estimate hazard ratios (HR) and 95% confidence intervals (CI) adjusting for relevant covariates. Results: After the 12-years follow-up period, moderate adherence to hPVG pattern was associated with lower all-cause and CVD mortality whereas greater adherence to uPVG pattern was associated with higher all-cause and CVD mortality. Compared with those in the lowest tertile, participants in the second tertile of adherence to the hPVG pattern showed a significant lower risk of all-cause mortality (HR = 0.59; 95%CI: 0.43, 0.82) and CVD mortality (HR = 0.47; 0.28, 0.78). Participants in the highest tertile of adherence to the uPVG showed an increased mortality risk of all-cause (HR = 1.53; 1.07, 2.19) and CVD (HR = 2.10; 1.19, 3.70). No significant associations were found between adherence to any of the PVG dietary patterns and cancer mortality. Conclusion: Moderate adherence to a healthy PVG pattern reduced the long-term mortality risk for all-cause and CVD in an older Mediterranean population, while higher adherence to an unhealthy PVG pattern increased the risk of all-cause and CVD mortality.